2009
DOI: 10.1111/j.1365-2133.2009.09327.x
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density in adult patients with moderate to severe atopic dermatitis

Abstract: We document a Z-score

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 30 publications
2
37
0
4
Order By: Relevance
“…Low bone mineral density was found in adult patients with moderate to severe atopic dermatitis, a chronic inflammatory skin disease [19]. Animal study showed when JunB was constitutively deleted from epidermal keratinocytes, a multi-organ disease developed affecting the skin, the hematopoietic system as well as the bone compartment [20].…”
Section: Discussionmentioning
confidence: 98%
“…Low bone mineral density was found in adult patients with moderate to severe atopic dermatitis, a chronic inflammatory skin disease [19]. Animal study showed when JunB was constitutively deleted from epidermal keratinocytes, a multi-organ disease developed affecting the skin, the hematopoietic system as well as the bone compartment [20].…”
Section: Discussionmentioning
confidence: 98%
“…6 Osteoporosis and osteopenia were detected in 4.8% and 32.8% of 125 adults with moderate-to-severe eczema, respectively. 31 Low BMD in these patients did not seem to respond to calcium and/or vitamin D supplementation. 32 Another small adult study found similar BMD between subjects with eczema and controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the chronic inflammation associated with eczema may predispose toward bone loss, as described in patients with rheumatoid arthritis and inflammatory bowel disease. 20,21 A 2009 study 22 found low BMD in approximately one-third of patients with moderate to severe atopic dermatitis (AD). Therefore, studies describing the prevalence of fracture among adults with eczema are needed.…”
mentioning
confidence: 99%